2022
DOI: 10.1177/23337214221117431
|View full text |Cite
|
Sign up to set email alerts
|

Mood Lifters for Seniors: Development and Evaluation of an Online, Peer-Led Mental Health Program for Older Adults

Abstract: Effective, scalable mental health programs are greatly needed for older adults. In this study, Mood Lifters—a peer-led, community-based program promoting mental well-being—was adapted to more specifically address the needs of older adults. Two groups completed the 14-week program via Zoom. A total of 24 participants enrolled ( Mage = 72 years), with 20 (83%) completing the program. Compared to baseline, program completers showed significant improvements in depression symptoms ( p < .01), perceived stress ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Nonetheless, our results elucidate the impact of CT specifically for young adults both in education and the workforce, and how they respond to treatment that caters to their unique needs. Our findings also indicate that young adults respond similarly well to ML when compared to middle-aged and older adults (Roberts et al, 2022; Votta & Deldin, 2022). Additionally, unlike previous findings (e.g., Negele et al, 2015), they suggest that there are no apparent differences in symptom severity in our sample of young adults with different degrees of CT. Another shortcoming of our study is that due to inadequate sample size, we could not tease apart the specific effects of all the forms of CT on clinical symptoms, which might differ from those of the overall CT value.…”
Section: Discussionsupporting
confidence: 71%
“…Nonetheless, our results elucidate the impact of CT specifically for young adults both in education and the workforce, and how they respond to treatment that caters to their unique needs. Our findings also indicate that young adults respond similarly well to ML when compared to middle-aged and older adults (Roberts et al, 2022; Votta & Deldin, 2022). Additionally, unlike previous findings (e.g., Negele et al, 2015), they suggest that there are no apparent differences in symptom severity in our sample of young adults with different degrees of CT. Another shortcoming of our study is that due to inadequate sample size, we could not tease apart the specific effects of all the forms of CT on clinical symptoms, which might differ from those of the overall CT value.…”
Section: Discussionsupporting
confidence: 71%
“…Mood Lifters was designed as a more accessible option for the general public, as compared to traditional mental health care. Prior evidence has shown that it is effective in the general adult population at reducing anxiety, depressive symptoms, and perceived stress (Votta and Deldin, 2022; Roberts et al , 2022; Prakash et al , under review). This paper aimed to determine Mood Lifters’ impact on individuals with a self-reported bipolar diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Participants and peer leaders were involved in the initial development of Mood Lifters, including providing feedback that was integrated throughout the current program. Although not specifically designed for individuals with bipolar disorder, feedback by participants, such as, “in twenty-two years, since my first diagnosis of bipolar disorder, I have not felt so stable in my life since I started Mood Lifters,” encouraged the current study team to consider whether Mood Lifters would be effective in this population especially as additional adaptations for other populations have proven successful (seniors, Roberts et al , 2022; graduate students, Prakash et al , 2023; pediatric palliative caregivers, Dews et al , 2023). Additionally, encouraging participation in a low-burden adjunctive treatment program during periods of euthymia (i.e.…”
Section: Mood Lifters For Individuals Who Self-reported As Bipolarmentioning
confidence: 99%
“…Other more medical interventions include cognitive behavior therapy (CBT), ECT biofeedback, heart rate variability feedback and antidepressants [40]. An example of an effective intervention is the peer-led combination of CBT, physical exercise and sleep activities on zoom (14 weeks) leading to decreased depression and stress and increased physical activity, brain health behavior and sleep quality [64]. But this study needs replicating as it is based on a very small sample (N=24 with only 20 completing the intervention).…”
Section: Sleep Deprivation Shanafimentioning
confidence: 99%